ISLAM AND NATIONALISM: The Role of the Universitas Al Washliyah In the Era of Post Independent 1950s - Faisal Riza (Journal of Contemporary Islam and Muslim Societies, 2021)
Abstract: This article attempts to explore the role of Al Washliyah University in the trajectory of modern Indonesian history, especially regarding the Islamic style they developed, the Islamic scientific authority built by both scholars and their teachings. In addition, this article examines the strategic position of the university in the 1950s socio-political setting in North Sumatra. This study is a historical study with a political sociology approach by prioritizing archival records, published historical sources, and making greater use of a wide range of oral material in the form of interviews. The results of this study indicate that UNIVA has bridged and developed the two main streams of public debate since the independence era and even now, namely regarding Islam and nationality. The thoughts of the founders have strengthened the integration between Islam and nationality in a formula to build a nation and a generation. Then, this affirmation is seen as important as the main argument in this article which allows the opening of a dialogue about how the Islamic scientific tradition that was built and developed by UNIVA scholars as a foundation for Islamic educators, actors of Islamic universities in promoting democratization and nationality, creating social cohesion. Keywords: UNIVA, Islamic higher education, Islamic authority, nationalism